Genome-Wide Comparative Analysis of Five Amaranthaceae Species Reveals a Large Amount of Repeat Content - Singh, Akshay; Maurya, Avantika; Rajkumar, Subramani; Singh, Amit Kumar; Bhardwaj, Rakesh; Kaushik, Surinder Kumar; Kumar, Sandeep; Singh, Kuldeep; Singh, Gyanendra Pratap; Singh, Rakesh (Plants (Basel), 2024)
Amaranthus is a genus of C4 dicotyledonous herbaceous plant species that are widely distributed in Asia, Africa, Australia, and Europe and are used as grain, vegetables, forages, and ornamental plants. Amaranth species have gained significant attention nowadays as potential sources of nutritious food and industrial products. In this study, we performed a comparative genome analysis of five amaranth species, namely, Amaranthus hypochondriacus, Amaranthus tuberculatus, Amaranthus hybridus, Amaranthus palmeri, and Amaranthus cruentus. The estimated repeat content ranged from 54.49% to 63.26% and was not correlated with the genome sizes. Out of the predicted repeat classes, the majority of repetitive sequences were Long Terminal Repeat (LTR) elements, which account for about 13.91% to 24.89% of all amaranth genomes. Phylogenetic analysis based on 406 single-copy orthologous genes revealed that A. hypochondriacus is most closely linked to A. hybridus and distantly related to A. cruentus. However, dioecious amaranth species, such as A. tuberculatus and A. palmeri, which belong to the subgenera Amaranthus Acnida, have formed their distinct clade. The comparative analysis of genomic data of amaranth species will be useful to identify and characterize agronomically important genes and their mechanisms of action. This will facilitate genomics-based, evolutionary studies, and breeding strategies to design faster, more precise, and predictable crop improvement programs.